Pengembangan Usaha Angkringan dengan Menggunakan Analisis SWOT - Agung Wijoyo; Agus Baskoro Hidayat; Ruslan Abu Honi; Sinta Nuriyah; Surya Adji Pangestu (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
An Angkringan business emerges and becomes a business because of the interaction of social relations between people, especially the middle and lower classes. This research aims to describe an Angkringan business with details to the public space that Akringan is a means of gathering place to build social closeness between the upper and lower middle class. Using descriptive qualitative methods and case studies, collecting data in the form of field observations and literature reviews. The advantages of this business are quite interesting, offering cheap drinks and food at affordable prices, providing a comfortable hangout facility and customers can linger to enjoy the atmosphere and dishes in Angkringan. And with the existence of Angkringan in public space makes a good social interaction relationship in socializing and gathering